Effect of Impedance-Shaping on Perception of Soft Tissues in Macro-Micro Teleoperation - Il Son, Hyoung; Bhattacharjee, Tapomayukh; Hashimoto, Hideki (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2012)
This paper aims at analyzing the effect of widely known impedance-shaping (IS) control method on the perception of soft tissues in telemicrosurgical applications. The generalized teleoperation control architecture has been modified to include the IS term. New performance index has been defined based on the two proposed indices for the detection and the discrimination of the soft environments to analyze the effect of this modified control on the kinesthetic perception of soft tissues. The effect is then theoretically analyzed on the conventional position-position, force-position, and four-channel control architectures based on the newly defined index. The effectiveness of this newly proposed kinesthetic perception index is also verified using psychophysics experiments. The theoretical analysis of the effects of the IS method on the perception of soft tissues is then validated using the proposed index by experiments with phantom soft tissues for conventional teleoperation architectures.
Keywords: BILATERAL TELEOPERATION; MULTILATERAL CONTROL; SCALED TELEOPERATION; TELEACTION SYSTEMS; FORCE SENSATION; DATA REDUCTION; TELEMANIPULATION; TELEPRESENCE; MICROMANIPULATION; TRANSPARENCY